Reviews of Books (International review of mission, 1955)
Book reviewed in this article: THE KNOWLEDGE AND PRACTICE OF CHRISTIANITY: Early Fathers from the Philokalia. Translated by E. Kadloubovsky and G. E. H. Palmer. London: Faber and Faber. 35s. 1954. THE MISSIONARY AND RELIGIOUS PEACE: Ruhe und Frömmigkeit. Ein Beitrag zur Lehre von der Missions-methode. By Thomas Ohm. A NORM FOR THE CHURCH TO COME: The Early Church and the Coming Great Church. By John Knox. THE APOCALYPSE IN THE WEST: The End of Time. By Josef Pieper. A SURVEY OF PAPAL CLAIMS: The Development of the Papacy. By H. Burn-Murdoch. LULL AND HIS VOCATION: Raymond Lulle—Docteur des Missions. By Ramon Sugranyes de Franch. EARLY FRANCISCAN MISSIONARIES IN THE EAST: The Mongol Mission: Narratives and Letters of the Franciscan Missionaries in Mongolia and China in the thirteenth and fourteenth centuries. Translated by a Nun of Stanbrook Abbey. Edited and with an Introduction by Christopher Dawson. HAZARDS OF MISSIONARY TRAVEL: Quand l'Europe Cherchait l'Asie. Jesuites Missionnaires (1541–1785). By Félix-Alfred Plattner. AN ADVENTUROUS AND CHALLENGING LIFE: Eighty Adventurous Years. The Autobiography of Sherwood Eddy. With an Introduction by Reinhold Niebuhr. ISLAM FROM ITS LITERARY SOURCES: Muhammad's People, A Tale by Anthology. By Eric Schroeder. AN ANTHOLOGY OF SUFISM: The Sufi Path of Love: An Anthology of Sufism. Compiled by Margaret Smith. THE SPIRITUAL ASPECT OF RACE RELATIONS: The Chosen People, or, The Bible, Christianity and Race. By Gerald W. Broomfield. London: Longmans. 4s. 1954.: The Numbered Days: South Africa and its Problems. By S. B. Jackman. ISLAM IN EAST AFRICA: Islam in East Africa. By Lyndon P. Harries. INDIAN SOCIOLOGISTS IN A HYDERABAD VILLAGE: Indian Village. By C. S. Dube. WORLD CHRISTIAN BOOKS: The Christians' God. By Stephen Neill. Christian Giving. By V. S. Azariah. Mark's Witness to Jesus Christ. By Eduard Lohse. Christianity and Science. By Charles E. Raven. INTERNATIONAL CHRISTIAN ENCOUNTER: The Blue Triangle. By Julian Duguid.